Pengaruh Profitabilitas, Leverage, Sales Growth terhadap Tax Avoidance dengan Ukuran Perusahaan sebagai Variabel Moderasi - Laurensia Josephine; Purwantoro; Enny Susilowati Mardjono; Juli Ratnawati (Politeknik Ganesha Medan, 2026)
This study scrutinizes tax avoidance behaviors within the healthcare sector by probing the interrelations among profitability, leverage, and sales growth, while positing firm size as a moderating determinant. The population encompasses all healthcare firms listed on the Indonesia Stock Exchange from 2021 to 2024. Samples were meticulously selected via purposive sampling according to predefined criteria, yielding 15 firms and a cumulative 60 observations. Employing a quantitative paradigm, the study draws on secondary data sourced from consolidated financial statements. Analytical procedures comprised descriptive statistics, classical assumption diagnostics, and Moderated Regression Analysis (MRA), with mean centering implemented to attenuate multicollinearity concerns. Empirical evidence demonstrates that profitability, debt-oriented capital structure, and sales growth wield substantive influence over tax avoidance, as operationalized by the Cash Effective Tax Rate (CETR). These findings elucidate that enhancements in financial performance and operational dynamism incentivize firms to engage more assiduously in tax management. Nonetheless, firm size does not exert a significant moderating effect on the nexus between profitability and leverage with tax avoidance. In contrast, firm size accentuates the impact of sales growth on tax avoidance. Consequently, large healthcare enterprises are predisposed to intensify tax planning initiatives concomitant with escalating sales.